REFIoT : A Framework to Combat Requirements Engineering in IoT Applications and Systems - Siakas, Errikos; Lampropoulos, Georgios; Rahanu, Harjinder; Georgiadou, Elli; Siakas, Dimitrios; Siakas, Kerstin (Springer, 2024)
In this research, we investigate the way in which Requirements Engineering is handled in the development of Internet of Things (IoT) applications. Successful and correct requirements engineering improves the quality of the development process and the whole system, as well as of the resulting products and services. As a result of an extensive literature review, and based on the authors’ collective longitudinal experience gained through industrial experience and ongoing research using a variety of software development approaches and practices, we identified and categorized the challenges in requirements elicitation and requirements engineering for IoT applications. We encapsulated the categorized requirements engineering challenges into REFIoT, a conceptual Requirements Engineering Framework for IoT, which can be used as a tool by requirements engineers in the development of IoT applications to identify risks so that they can be minimized at an early stage of systems development using the values of the SPI Manifesto we propose mitigation actions.
Keywords: Requirements Engineering; Requirements Management; Requirements Development; Requirements Elicitation; Internet of things; fi=Tuotantotalous|en=Industrial Management|